2021
DOI: 10.1002/ijc.33830
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant docetaxel plus carboplatin vs epirubicin plus cyclophosphamide followed by docetaxel in triple‐negative, early‐stage breast cancer (NeoCART): Results from a multicenter, randomized controlled, open‐label phase II trial

Abstract: Background: Previous studies have shown that the addition of carboplatin to neoadjuvant chemotherapy regimens improved the pathologic complete response (pCR) rate in patients suffering from triple-negative breast cancer (TNBC). However, no studies have assessed the effects of the combination of docetaxel and carboplatin without anthracycline with taxane-and anthracycline-based regimens.Methods: The NeoCART study was designed as a multicenter, randomized controlled, open-label, phase 2 trial to assess the e cac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…A previous study involving two independent prospective cohorts reported a pCR rate of 55% with the treatment of neoadjuvant carboplatin plus docetaxel for TNBC patients, which was comparable with the pCR rates achieved with the treatment of neoadjuvant carboplatin plus anthracycline‐taxane chemotherapy 32 . Recently, the randomized controlled NeoCART study first demonstrated that neoadjuvant docetaxel plus carboplatin achieved a higher pCR rate compared with conventional anthracycline‐taxane followed taxanes regimens for TNBC patients (61.4% vs 38.6%, P = .004), and the survival outcomes were comparable 33 …”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…A previous study involving two independent prospective cohorts reported a pCR rate of 55% with the treatment of neoadjuvant carboplatin plus docetaxel for TNBC patients, which was comparable with the pCR rates achieved with the treatment of neoadjuvant carboplatin plus anthracycline‐taxane chemotherapy 32 . Recently, the randomized controlled NeoCART study first demonstrated that neoadjuvant docetaxel plus carboplatin achieved a higher pCR rate compared with conventional anthracycline‐taxane followed taxanes regimens for TNBC patients (61.4% vs 38.6%, P = .004), and the survival outcomes were comparable 33 …”
Section: Discussionmentioning
confidence: 58%
“…32 Recently, the randomized controlled NeoCART study first demonstrated that neoadjuvant docetaxel plus carboplatin achieved a higher pCR rate compared with conventional anthracycline-taxane followed taxanes regimens for TNBC patients (61.4% vs 38.6%, P = .004), and the survival outcomes were comparable. 33 Dose-dense chemotherapy shortens the treatment cycle and increases the dose intensity thus improving anti-tumor efficacy, which has been recommended as a routine postoperative adjuvant chemotherapy option. 34,35 Studies have demonstrated that dose-dense taxanes could significantly improve the pCR rate and long-term survival of patients with early-stage high-risk breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…38.6%, P = 0.044), with a pCR increase of 22.8% 17 . The data of this investigation are consistent with the NeoCART trial, although the absolute increase in pCR in this trial (16.1%) was smaller, likely due to the higher tumor burden of participants, with 63% of patients having node-positive tumors, including those with N3 involvement.…”
Section: Discussionmentioning
confidence: 91%
“…The results of our study indicated promising antitumor activity of the combination of apatinib and standard chemotherapy. NeoCART study, 51 a multicenter, randomized controlled, phase II trial conducted by our institution to assess the efficacy and safety of docetaxel plus carboplatin versus EC-D in untreated stage II-III TNBC, showed that the rate of pCR in the EC-D group was 38.6%. Since the rate of pCR (54.8%) achieved in combination of apatinib and standard chemotherapy was dramatically higher than that of chemotherapy alone (38.6%), there may exist promising synergistic effect between apatinib and standard chemotherapy.…”
Section: Discussionmentioning
confidence: 99%